2001
DOI: 10.1161/01.cir.103.6.897
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation of Postnatal Neovascularization With Autologous Bone Marrow Transplantation

Abstract: Background-Endothelial progenitor cells (EPCs) have been identified in adult human peripheral blood. Because circulating EPCs should originate from bone marrow (BM), we examined whether BM mononuclear cells (BM-MNCs) can give rise to functional EPCs and whether transplantation of autologous BM-MNCs might augment angiogenesis and collateral vessel formation in a rabbit model of hindlimb ischemia. Methods and Results-Rabbit BM-MNCs were isolated by centrifugation through a Histopaque density gradient and culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
296
3
12

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 431 publications
(322 citation statements)
references
References 41 publications
11
296
3
12
Order By: Relevance
“…We and other investigators recently reported that transplantation of culture-expanded human EPCs augmented ischemia-induced angiogenesis in vivo (Kalka et al, 2000;Murohara et al, 2000). Similarly, direct implantation of autologous BM-MNCs containing EPCs has been shown to augment angiogenesis in ischemic tissues (Shintani et al, 2001b, Tateishi-Yuyama et al, 2002. Thus, cell transplantation appears to be an effective means for therapeutic neovascularization.…”
Section: Discussionmentioning
confidence: 78%
“…We and other investigators recently reported that transplantation of culture-expanded human EPCs augmented ischemia-induced angiogenesis in vivo (Kalka et al, 2000;Murohara et al, 2000). Similarly, direct implantation of autologous BM-MNCs containing EPCs has been shown to augment angiogenesis in ischemic tissues (Shintani et al, 2001b, Tateishi-Yuyama et al, 2002. Thus, cell transplantation appears to be an effective means for therapeutic neovascularization.…”
Section: Discussionmentioning
confidence: 78%
“…In some animals, we saw an extensive infiltration of necrotic gastrocnemius muscle with T lymphocytes and dendritic cells, some of which were GFP + and hence donor in origin. Many preclinical studies have evaluated the benefits of mBMC transplantation in limb ischemia (5,43,44); however, in most studies, cells were injected only in the upper part of the limb, where inflammation due to necrosis is limited, which may have precluded the detection of the contribution of grafted immune cells to the inflammatory reaction. While we used unfractionated BMCs, in most clinical studies, only the mononuclear fraction or subsets of these are used (Supplemental Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…(3,(6)(7)(8)(9) According to the literature, CLI complicates the course of eliminating atherosclerosis of the lower limbs in 33% of patients. (6,(10)(11)(12) As a result, the lethality and number of amputations now reaches 14.0% and 20.4%, respectively, in CLI patients after reconstructive interventions on the vascular bed. ( Reconstructive surgical interventions provide preservation of limbs in the postoperative period in terms up to 5 years in 80% of patients, up to 10 years -only in 50%.…”
Section: Introductionmentioning
confidence: 99%